The Effects of Exercise on Natriuretic Peptides in Individuals without Heart Failure - Hidetaka Hamasaki (MDPI AG, 2016)
Cardiac natriuretic peptides (NPs) play an important role in the regulation of energy expenditure in skeletal muscle and adipose tissue. A systematic review on the effects of exercise on NPs in patients with heart failure reported that aerobic and resistance training reduced NPs; however, the effects of exercise on NPs and the underlying mechanism of exercise-induced NP secretion in subjects without heart failure remain unknown. In athletes and young, healthy subjects, the NP concentration at rest is not elevated, but strenuous endurance exercise significantly increases NPs. The exercise-induced increase in NPs may be caused by transient myocardial wall stress, cardiomyocyte metabolic changes, or neuroendocrinological response, which may have cytoprotective and growth-regulating effects on the heart. On the other hand, in elderly, overweight/obese subjects, and patients with hypertension, NP concentrations also increase during exercise; however, NP secretion may be more susceptible to cardiac stress compared to young, healthy individuals. Recent studies have shown that NPs are associated with thermogenesis in fat tissue and oxidative capacity in skeletal muscles. NPs may also have a protective role for skeletal muscle in humans, although further studies are warranted to elucidate the physiological mechanism of exercise-induced NP secretion.